The practice of federalism under the constitutions of Nigeria, United States of America and Australia (2022)
The concept of federalism is an unsettled phenomenon in political and legal disciplines; though many writers have common areas of agreement as to what the basic principles of federalism entail. This chapter is meant to consider the concept of federalism and some of its components with the aim of determining the true features of the concept. The chapter further considers the practice of federalism in the United States of America, Australia and Nigeria with the purpose of comparing these with the basic requirements of federalism. The chapter finds that though there is no perfect practice of federalism in the three countries but there is a real legal and Constitutional template for a true practice of federalism in the United States and Australia even though there are some areas of concession or compromise by the federating units and the courts giving extensive interpretation of the scope of powers of the central government under some omnibus provisions. In Nigeria, on the other hand, the Constitutional structure of power does not really reflect a true federal arrangement. However, the country continues to struggle for survival as a unit under this lopsided arrangement.